The Role of Strategic Leadership Dimensions in Achieving the Strategic Capabilities - yousif, Mehvan Sh.; Ahmed, Aveen M.S. (Humanities Journal of University of Zakho, 2017)
This research aims to investigate the role of strategic leadership dimensions in achieving the strategic capabilities at university of Zakho, and the university of Zakho was selected to perform the practical field of the research and the sample of research included (80) from the teaching staff, a form of questionnaire was designed for data collection, the data were analyzed using several statistical tools. The most important of research conclusions are: A positive significant correlation between strategic leadership dimensions and strategic capabilities in surveyed university, and a positive significant effect from strategic leadership dimensions in strategic capabilities in surveyed university. The research found a set of proposals the most important of them was: it is necessary for university management of Zakho to work for allocate a budget to invest in modern technology means through the purchase of modern techniques to be ensures generate the knowledge for her staff.